"WHITE CRISIS" AND/AS "EXISTENTIAL RISK, " OR THE ENTANGLED APOCALYPTICISM OF ARTIFICIAL INTELLIGENCE: with Robert M. Geraci and Simon Robinson, "Introduction to the Symposium on Artificial Intelligence and Apocalypticism"; Beth Singler, "Existential Hope and Existential Despair in AI Apocalypticism and Transhumanism"; Michael Morelli, "The Athenian Altar and the Amazonian Chatbot: A Pauline Reading of Artificial Intelligence and Apocalyptic Ends"; Victoria Lorrimar, "Mind Uploading and Embodied Cognition: A Theological Response"; and Syed Mustafa Ali, "'White Crisis' and/as 'Existential Risk, ' or the Entangled Apocalypticism of Artificial Intelligence.". Issue 1 (17th February 2019) - Ali, Syed Mustafa
Abstract: In this article, I present a critique of Robert Geraci's Apocalyptic artificial intelligence (AI) discourse, drawing attention to certain shortcomings which become apparent when the analytical lens shifts from religion to the race–religion nexus. Building on earlier work, I explore the phenomenon of existential risk associated with Apocalyptic AI in relation to "White Crisis, " a modern racial phenomenon with premodern religious origins. Adopting a critical race theoretical and decolonial perspective, I argue that all three phenomena are entangled and they should be understood as a strategy, albeit perhaps merely rhetorical, for maintaining white hegemony under nonwhite contestation. I further suggest that this claim can be shown to be supported by the disclosure of continuity through change in the long‐durée entanglement of race and religion associated with the establishment, maintenance, expansion, and refinement of the modern/colonial world system if and when such phenomena are understood as iterative shifts in a programmatic trajectory of domination which might usefully be framed as "algorithmic racism."